Business cycle asymmetries and the labor market - Kohlbrecher, Britta; Merkl, Christian (Journal of Macroeconomics, 2022)
This paper shows that a search and matching model with idiosyncratic training cost shocks can explain the asymmetric movement of the job-finding rate over the business cycle and the decline of matching efficiency in recessions. Large negative aggregate shocks move the hiring cutoff into a part of the training cost distribution with higher density. The position of the hiring cutoff in the distribution is disciplined by the empirical elasticity of the job-finding rate with respect to market tightness. Our model explains a large fraction of the matching efficiency decline during the Great Recession and generates state-dependent effects of policy interventions.<br
CRIS-Team Scopus Importer:2022-08-05
Keywords: Beveridge curve; Job-finding rate; Labor market asymmetries; Matching function; Policy effectiveness; Unemployment

Hartz IV and the decline of German unemployment: A macroeconomic evaluation - Hochmuth, Brigitte; Kohlbrecher, Britta; Merkl, Christian; Gartner, Hermann (Journal of Economic Dynamics & Control, 2021)
This paper proposes a new approach to evaluate the macroeconomic effects of the “Hartz IV” reform, which reduced the generosity of long-term unemployment benefits. We propose a model with different unemployment durations, where the reform initiates both a partial effect and an equilibrium effect. We estimate the relative importance of these two effects and the size of the partial effect based on the IAB Job Vacancy Survey. Our approach does not hinge on an external source for the decline in the replacement rate for long-term unemployed. We find that Hartz IV was a major driver for the decline of Germany’s steady state unemployment and that partial and equilibrium effect were of equal importance. In addition, we provide direct empirical evidence on labor selection, one potential dimension of recruiting intensity.<br
Keywords: Unemployment benefits reform; Search and matching; Hartz reforms

Revisiting the matching function - Kohlbrecher, Britta; Merkl, Christian; Nordmeier, Daniela (Journal of Economic Dynamics & Control, 2016)
There is strong empirical evidence for Cobb–Douglas matching functions. We show in this paper that this widely found relation between matches on the one hand and unemployment and vacancies on the other hand can be the result of different underlying mechanisms. Obviously, it can be generated by assuming a Cobb–Douglas matching function. Less obvious, the same relationship results from a vacancy free-entry condition and idiosyncratic productivity shocks. A positive aggregate productivity shock leads to more vacancy posting, a shift of the idiosyncratic selection cutoff and thereby more hiring. We calibrate a model with both mechanisms to administrative German labor market data and show that idiosyncratic productivity for new contacts is an important driver of the elasticity of the job-finding rate with respect to the market tightness. Accounting for idiosyncratic productivity can explain the observed negative time trend in estimated matching efficiency and asymmetric business cycle responses to large aggregate shock
Keywords: Matching function; Idiosyncratic productivity; Job creation; Vacancies; Time trend; Asymmetries

The effects of productivity and benefits on unemployment: Breaking the link - Brown, Alessio J.G.; Kohlbrecher, Britta; Merkl, Christian; Snower, Dennis J. (Economic Modelling, 2021)
In the standard macroeconomic search and matching model of the labor market, there is a tight link between the quantitative effects of (i) aggregate productivity shocks on unemployment and (ii) unemployment benefits on unemployment. This tight link is at odds with the empirical literature. We show that a two-sided model of labor market search where the household and firm decisions are decomposed into job offers, job acceptances, firing, and quits can break this link. In such a model, unemployment benefits affect households' behavior directly, without having to run via the bargained wage. A calibration of the model based on U.S. JOLTS data generates both a solid amplification of productivity shocks and a moderate effect of benefits on unemployment. Our analysis shows the importance of investigating the effects of policies on the households' work incentives and the firms' employment incentives within the search process.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Aggregate shocks; Macro models of the labor market; Search and matching; Unemployment benefits